Ein Schminkgefäß und ein General - Jansen-Winkeln, Karl (Zeitschrift für ägyptische Sprache und Altertumskunde, 2016)
The cosmetic vase Durham EG3995, probably from the Early Dynastic period, was reused by a high military commander as a votive in the time of Apries. In its inscription, an anonymous person asks Sakhmet/Hathor, possibly during a ceremony by which the vessel was consecrated for use in the temple, to reward the General for his donation with royal favour and a good reputation. The military title mr mnfyt of the donor and the meaning of mnf Ꜣ t/mnfyt is discussed: the mnfyt were probably troops transported by ship.